KAJIAN ADAPTASI TIGA VARIETAS MELON DAN PEMBERIAN PUPUK ORGANIK CAIR KE DATARAN RENDAH TERHADAP HASIL - Sumartono, Sumartono; Tini, Eti Wuki; Saridewi, Prita (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
Melon growing demand due to increasing population, increasing public awareness of nutritional value and vitamins, as well as the per capita income of the population increased. Efforts to meet the demand of melon can be done with proper cultivation techniques with organic fertilizers so that food safety is guaranteed. The purpose of the study was to find a melon organic fertilizer of several varieties. In addition to knowing the adaptability of three varieties of melon in the lowlands as the material for the assembly of new varieties. The method used is the experiment with the complete randomized block design with three varieties (Action 434 varieties, Jade Dew varieties , Golden Aroma varieties, and four kind of organic fertilizer, that are liquid organic fertilizer P1D1 Grow, liquid organic fertilizer, Organox, and liquid organic fertilizer Nasa The result showed that the best growth (length of the plant and chloroil) is shown by the varieties of Action 434. The highest yield reached 1,94 kg. The organic fertilizer is good is Organox